Modified global and modified linear contrast stretching algorithms: New colour contrast enhancement techniques for microscopic analysis of malaria slide images - Aimi Salihah, Abdul-Nasir; Mohd Yusoff, Mashor, Prof. Dr.; Zeehaida, Mohamed, Dr. (Hindawi Publishing Corporation, 2013)
Link to publisher's homepage at http://www.hindawi.com/